Public Sector Accounting and Auditing in South Asia : A Comparison to International Standards - World Bank (World Bank, 2012)
This report aims to support regional collaboration and renewed collective efforts to strengthen financial management and oversight practices in South Asia. It compares the public sector accounting and auditing practices in eight South Asian countries to international standards. It is intended to inform public sector accounting and auditing authorities, primarily Ministries of Finance, accountants general, and auditors general, and support their efforts to provide senior policy makers and the general public in their countries with credible, relevant, and useful financial information about the collection, management, and use of public resources. This report is based on detailed 'gap analysis' assessments that were prepared in recent years in Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka, providing comparisons of public sector accounting and auditing practices in those countries to international standards. This report is a synthesis of the gap analysis reports.